APPLICATION OF THE METHOD OF PREVENTIVE DIAGNOSIS IN THE MANAGEMENT OF INSTITUTIONS OF HEALTH SERVICES IN TIMES OF CRISIS - T. T. Taygibova (Вестник Дагестанского государственного технического университета: Технические науки)
This article discusses the basic problems of management of institutions of health services in times of crisis, in the framework of the methodology for preventive diagnosis. Analyze the purpose and principles of preventive diagnosis techniques, providing a choice of adequate managerial influence on the institution of health services for the purpose of leveling the sources of origin of the crisis factors. The problem of diagnosis of the crisis of institutions of health services in the context of the management of the relations arising in the process of the formation mechanism of crisis management. A model of interaction elements of the mechanism of crisis management agencies of health services.